Romska naselja kot poseben del naselbinskega sistema v Sloveniji - Zupančič, Jernej (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
The paper analyse the Roma-settlements as a specific phenomenon of slovene settlement system. Roma people changed their way of life from nomadism to stabile settlement very late (in aftewar period) and remain some specifics in living-standard and have poor opportunities for social integration. That s why they have a lot of social problems, as well as confrontations and conflicts with local neighbours. But the situation is not perspectiveless: helped by local and national factors, some of Roma people are able to advance their standard of living, what makes, by the same time, the relations with other local population better.
Keywords: Slovenia; Slovenija; etnične skupine; Romi; poselitev; naselja; geografija naselij